AKTIVITAS ANTIOSTEOPOROSIS EKSTRAK ETANOL 96 % DAUN Abelmoschus manihot L. MEDIK SECARA IN VITRO MENGGUNAKAN SEL PREOSTEOBLAS MC3T3-E1 - Agnis Pondinekaria Aditama; Mangestuti Agil; Hening Laswati (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Osteoporosis is a disease characterized by low bone mass and structural deterioration of bone tissue. Estrogen deficiency causes loss of bone mineral density which causes osteoporosis. Phytoestrogen is a potential alternative of estrogen that can be used as Hormone Replacement Therapy on osteoporosis with minimum side effects. Many edible plants contain phytoestrogens that are believed to promote bone health. Abelmoschus manihot (L.) Medik has been known as a plant that is empirically used in the traditional medicine and has potency to prevent osteoporosis. The aim of this research is to determine whether the Abelmoschus manihot (L.) Medik leaves have the potential to increase bone formation in an in vitro assays using preosteoblast cell line MC3T3-E1. The results showed an increasing activity of Alkaline phosphatase using confocal laser scanning microscopy technique.